ANALISIS PENGARUH MODAL KERJA PRODUKTIF, PELATIHAN, DAN PENDAMPINGAN TERHADAP PENINGKATAN PENDAPATAN MUSTAHIK - Aini, Riza Nurul; Suprapto, Eddy (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Income disparity and poverty are one of the real problems faced by Indonesia (Yahya et.al, 2010). One of the efforts by the government to overcome poverty is the empowerment of micro, small and medium enterprises or UMKM. Empowerment of UMKM with the combination of ZIS is able to realize productive efforts that conform to Islamic law. This study aims to analyze the effect of productive working capital, training, and assistance on the increase in impossible income in Trenggalek Regency National High School. The approach used in this study is a quantitative approach using multiple linear regression analysis methods. The data types in this study are primary and secondary data derived from questionnaires, documentations, and other literature. The respondents in this study were 42 respondents with the criteria, which is impossible for recipients of productive economic assistance from the National Baznas of Trenggalek Regency. Research results show that simultaneous capital productive employment, training, and assistance have a significant effect on the increase in impossible income. Partially productive working capital and training had a positive and significant effect on the increase in impossible income, while assistance had a negative and significant effect on the increase in impossible income.